PENATAAN PEDAGANG KAKI LIMA PADA PASAR ATAS DAN PASAR BAWAH KOTA BUKITTINGGI - Dian Azhari; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
City of Bukittinggi is one of the cities that were targeted urban people to create jobs in the informal street vendors (PKL). Street vendors who sell in locations forbidden lead the market becomes well ordered. The problem in this research is how the arrangement of street vendors by the Market Management Department in coordination with municipal police in the market above and below market Bukittinggi and the factors that influence the arrangement of street vendors in the market up and down markets such Bukittinggi. The purpose of this study was to find out how the arrangement of street vendors by the Market Management Department in coordination with municipal police in Upper and Lower Market Markets Bukittinggi and to determine the factors that influence the arrangement by the Department of Market Management in Bukittinggi The concept used is the management theory, proposed by George R. Terry who see management policies based on four criteria, namely: planning, organizing, actuating, and controlling. The purpose of this study was to review the structuring of street vendors in the Market Up and Down Markets Bukittinggi, as well as any factors that influence it. This study uses a qualitative assessment of descriptive data. In the data collection researchers use interviewing techniques, observation and documentation using snowball sampling method as sources of information and data analysis with triangulation techniques. The results show that the arrangement of street vendors in the city of Bukittinggi is still not running well, but in application implementation has begun to appear visible, but nonetheless it still took the development of the parties concerned how should this arrangement could go better, in order to attain a uncomfortable for the visitors in the Upper and Lower Market Markets Bukittinggi. But in this case, we recommend that the government should provide special land and special time for vendors in both the Upper and Lower Market Markets Bukittinggi, so it is expected to be efforts in achieving the desire of all parties. Keywords: Planning, organizing, actuating, controlling, regulation, Street vendors